Konsep New Normal dalam Perspektif Hukum Islam - Muhammad Erfan Muktasim Billah (Nizham Jurnal Studi Keislaman, 2020)
During times of great crisis like the Covid-19 pandemic today, individuals and communities consult their moral systems for support and countermeasures mechanisms. For the Islamic religious community, the ritual of worshippers makes an integral part of this causational mechanism, which strengthens their relationship with God, Almighty, who can provide the best support. However, more and more scientific evidence is supported by the WHO guidelines, urging people and governments to postpone or cancel mass meetings because it contains a risk of spreading new viruses. At first, Muslim religious scholars looked fragmented, and sometimes even confused, on how to incorporate new scientific data in religious-ethical discourse that has long been in the rituals of pilgrims one of the procedures for the funeral of Muslims.